VIRULENCE PROFILE OF BULGARIAN CLINICAL ISOLATES STREPTOCOCCUS AGALACTIAE - PCR DETERMINATION - Adile Muhtarova; Raina Gergova; Ivan Mitov (Peytchinski Publishing, 2020)
Purpose: This study aims to determine the virulence profile of the circulating Bulgarian clinical isolates of GBS including the highly virulent serotype III by molecular methods and evaluate the differences among studied isolates from healthy pregnant women and non-pregnant ill persons. Material and methods: We investigated 104 non-duplicate isolates of GBS obtained from pregnant (n=15) and non-pregnant women (n=89), living in Sofia, Bulgaria. All GBS strains were screened for the presence of important virulence genes, namely bca, cyl(E), rib, hyl(B) and the capsular serotype III detected by Real-time PCR. Results: PCR detection of five important virulence genes showed that cylE (91.3%) was the most prevalent one among the total isolates of GBS. Genes encoding the C protein (bca), hyaluronate lyase (hylB), Alp family protein Rib (rib) were presented in 51%, 17.3% and 22.1% respectively of the examined isolates. By using real-time PCR, we found that 13.5% from all tested Bulgarian GBS strains confirmed as GBS serotype III and harbored cpsI gene. No significant differences between the two groups were observed excluding the presence of cpsI. Conclusion: The risk of neonatal and prenatal GBS infection in 1/3 of healthy pregnant women colonized by streptococcal strains with highly virulent capsular serotype in combination with other strong virulent factors was demonstrated by this study. The regular screening for GBS and properly treatment could be reduce the severe maternal-fetal infections due to this microorganism.